Typification and redelimitation of Nepenthes alata with notes on the N. alata group, and N. negros sp. nov. from the Philippines. (22nd August 2013) - Cheek, Martin; Jebb, Matthew
<x xml:space="preserve">Abstract</x> In the course of studies to typify what has been regarded as the most widespread and common of the endemic Philippines species of Nepenthes, N. alata Blanco, we were able to review the morphological variation in what we previously regarded as a polymorphic species. This led us to redelimit that species in a narrower sense, to resurrect N. graciliflora Elmer, and to recognise N. negros sp. nov., here assessed as 'Critically Endangered' (CR) using the IUCN standard. The Nepenthes alata group is characterised and a key to its species is provided.